Defective Titanium Dioxide-supported Ultrasmall Au Clusters for Photocatalytic Hydrogen Production - Zhang, Xiaoqin; Zhang, Wenna; Xu, Yuanmei; Jin, Mingliang (Frontiers in Physics, 2020)
Ultrasmall precious metal clusters have attracted extensive attention for providing a very specific surface and promoting electron transfer. In this work, ultrasmall Au clusters based on defective TiO2 nanosheets (Au/D-TiO2) were prepared and introduced into photocatalytic hydrogen evolution (PHE). Different defects of TiO2 nanosheets (D-TiO2) were constructed using a heating process and then loaded with Au clusters. Compared with bare TiO2, Au clusters established on defective TiO2 nanosheets with a narrower band gap showed higher light absorption performances, resulting in obviously enhanced photocatalytic hydrogen production performances. The Au/D-TiO2 displayed the greatly enhanced PHE activity of 3142.33 μmol•h-1•g-1, which was over 45 times than the pure TiO2. The results showed that the catalysts had good prospects in the field of photocatalytic hydrogen production.